Analysis of quality and technical and economic indicators of the technology for the production of packaged meat and bone broths with long shelf life - Fomenko O. S.; Rudik F. Ya. (Vestnik MGTU)
The paper contains the analysis of technological and economic aspects of the production of packaged meat-and-bone broths with long shelf life. The study focuses on comparing traditional technology with a new method that integrates ultraviolet treatment of raw materials and ultrasonic treatment of the finished product. The assessment includes microbiological indicators, production costs, and profitability. The study has demonstrated that the application of preliminary UV-amalgam treatment of meat-and-bone raw materials, combined with ultrasonic homogenization and sterilization of the finished broth, significantly reduces the time required to achieve microbiological safety from 11 to 1 hour. Furthermore, the use of this technology reduced production costs by 33.7 %, while profitability increased from 316.4 to 528.7 %. The study also analyzes the costs associated with creating and operating the flow-technological line, allowing for an overall evaluation of its economic efficiency. The results confirm the economic feasibility of implementing the new technology in the food industry, making it a promising solution for enhancing the competitiveness of products in the market. The economic benefits are driven by reduced production costs and extended shelf life of the finished product.